1-{(1Z)-1-[3-(2,4-Dichlorophenoxy)propoxy]-1-(2,4-difluorophenyl)prop-1-en-2-yl}-1H-1,2,4-triazole - Luan, Yuan-yuan (International Union of Crystallography, 2012)
In the title compound, C(20)H(17)Cl(2)F(2)N(3)O(2), the triazole ring makes dihedral angles of 28.0 (3) and 72.5 (2)° with the 2,4-dichloropheny and 2,4-difluorophenyl rings, respectively, and the molecule adopts a Z-conformation about the C=C double bond. In the crystal, C—H⋯O and C—H⋯N hydrogen bonds link the molecules.